A convenient 'NOSE' approach used towards the synthesis of 6-amino-1, 3-dimethyl-5-indolyl-1H-pyrimidine-2, 4-dione derivatives catalyzed by nano-Ag. (5th January 2016) - Das, Vijay Kumar; Bharali, Pranjal; Konwar, Bolin Kumar; Mikkola, Jyri-Pekka; Shchukarev, Andrey; Thakur, Ashim Jyoti
Abstract : Uracil derivatives were synthesized in high yield catalyzed by reusable nano-Ag at 70 °C upon reacting 6-amino-1, 3-dimethyluracil and indole derivatives. Abstract : An endeavour has been made towards the synthesis of uracil based compounds in good to high yield catalyzed by nano-Ag at 70 °C upon reacting 6-amino-1, 3-dimethyluracil and indole derivatives. The catalyst was potentially recyclable from fresh up to the third run.